Self-branding strategies of online freelancers on Upwork - Blyth, Dorothy Lee; Jarrahi, Mohammad Hossein; Lutz, Christoph; Newlands, Gemma (New media & society, 2024)
Self-branding is crucial for online freelancers as they must constantly differentiate themselves from competitors on online labor platforms to ensure a viable stream of income. By analyzing 39 interviews with freelancers and clients on the online labor platform Upwork, we identify five key self-branding strategies: boosting a profile, showcasing skills, expanding presence, maintaining relationships with clients, and individualizing brand. These self-branding strategies are contextualized within Goffman’s dramaturgical theory and through an affordances lens, showing immanent tensions. While online freelancers successfully leverage self-branding to improve their visibility on Upwork and beyond, the client perspective reveals a fine line between too little and too much self-branding. Online freelancers must brand themselves in visibility games when the game rules are largely opaque, riddled with uncertainty, and constantly evolving. We connect the findings to adjacent platform economy research and derive a self-branding as a performance framework.